Role of the bZIP protein Atf3 in metabolic and immune homeostasis and Molecular interactions of the insect juvenile hormone receptor Met - Ryneš, Jan (Jihočeská univerzita, 2012)
This thesis comprises two parts: I. Role of the bZIP protein Atf3 in metabolic and immune homeostasis This part of the thesis is based on analysis of loss-of-function phenotypes of the bZIP transcription factor Atf3 in Drosophila larvae. By employing genetic, biochemical, molecular and microscopic techniques, metabolic and immune disorders caused by atf3 mutation have been characterized, suggesting a new role of Atf3 as a common regulator of metabolism and immunity in Drosophila. II. Molecular interactions of the insect juvenile hormone receptor Met In the second part of the thesis, ligand-binding properties of the candidate insect juvenile hormone (JH) receptor, the bHLH PAS transcription factor Met, have been investigated. It has been proven that Met binds JH with high affinity and point mutations disrupting JH binding have been identified. By using biochemical tools, JH-dependent protein-protein interactions of Met have been tested. The results show that Met senses the JH signal by specifically binding the hormonal ligand, thus establishing the function of Met as a JH receptor.
Role of the bZIP protein Atf3 in metabolic and immune homeostasis and Molecular interactions of the insect juvenile hormone receptor Met